Integrating Flipped Classroom Into Oral Presentation to Enhance Students’ Speaking Achievement - Rella Islami; Feni Munifatullah; Ujang Suparman (Yayasan Darusssalam Bengkulu, 2026)
This study investigated the impact of applying the Flipped Classroom approach to oral presentation activities in order to improve the speaking performance of EFL learners. The research was grounded in the crucial role of oral presentations in global communication and the challenges students often face due to limited preparation time, despite its importance for content mastery. Using a quasi-experimental design, the study involved two classes of third-year students at Lazuardi Haura Junior High School, with a total of 30 participants. An Independent Group T-test was employed to compare the post-test results of the experimental and control groups, while the speaking scores of the experimental group across multiple assessments were analyzed using a One-Way Repeated Measures ANOVA. Data were collected through pre-tests and post-tests over six meetings and processed using SPSS. Both groups showed improvement, but the experimental group achieved a larger score increase, with fluency identified as the most enhanced aspect. The results demonstrate that the Flipped Classroom fosters stronger speaking performance through self-directed learning, active participation, personalization, and technology-supported practice.